Three-dimensional in vivo evaluation of the cornea in patients with unilateral posterior interstitial keratitis - Gu, Shao-Feng; Gao, Shuang; Wang, Hai-Kun; He, Lin-Hui; Peng, Rong-Mei; Xiao, Ge-Ge; Hong, Jing (Frontiers in Medicine, 2023)
Purpose The purpose of this study was to investigate the in vivo morphologic features of the cornea in patients with unilateral posterior interstitial keratitis. Methods Seven eyes of 7 patients with unilateral posterior interstitial keratitis were examined by slit-lamp biomicroscopy, anterior segment optical coherence tomography (AS-OCT), and in vivo confocal microscopy (IVCM). The imaging features of the cornea were evaluated and analyzed. Results By slit-lamp examination, the posterior corneal stromal opacities were observed in all 7 eyes, and deep neovascularization in 4 eyes. The posterior stromal opacities showed higher reflectivity with an intact overlying epithelium by AS-OCT and did not invade the Bowman’s layer in all cases. IVCM revealed highly reflective dispersed microdots, needle-shaped bodies, and increased reflectivity of keratocytes in the lesion site in all patients. Active Langerhans cells and an attenuated subbasal nerve plexus were observed in 5 eyes. After treatment, the active Langerhans cells disappeared; however, highly reflective microdots and needle-shaped bodies remained. Conclusion The three-dimensional evaluation of slit-lamp biomicroscopy, AS-OCT, and IVCM may help in the early diagnosis of patients with posterior interstitial keratitis.